2016
DOI: 10.1109/tcomm.2016.2614311
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-ADC Massive MIMO Uplink in Frequency-Selective Channels

Abstract: The aim of this paper is to investigate the recently developed mixed-ADC architecture for frequency-selective channels. Multi-carrier techniques such as orthogonal frequency division multiplexing (OFDM) are employed to handle inter-symbol interference (ISI). A frequency-domain equalizer is designed for mitigating the inter-carrier interference (ICI) introduced by the nonlinearity of one-bit quantization. For static single-input-multiple-output (SIMO) channels, a closed-form expression of the generalized mutual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 38 publications
(99 reference statements)
0
32
0
Order By: Relevance
“…LEMMA 1 Lemma 1. The analog beamforming gain within the cell l, c llk , defined in (8) is bounded as follows…”
Section: Appendix Bmentioning
confidence: 99%
See 1 more Smart Citation
“…LEMMA 1 Lemma 1. The analog beamforming gain within the cell l, c llk , defined in (8) is bounded as follows…”
Section: Appendix Bmentioning
confidence: 99%
“…Furthermore, the spectral efficiencies of a mixed-ADC system under energy constraint has been studied in [7]. The mixed-ADC architecture in frequency-selective channels has been investigated in [8]. It has been demonstrated in [9] that low-precision, e.g., 2-3 bits, ADCs only cause limited sum rate loss under some mild assumptions for an amplifyand-forward relay uplink network.…”
mentioning
confidence: 99%
“…As indicated by the capacity derivation for additive white Gaussian noise (AWGN) channels in [4], only 10%-20% of capacity is lost under the quantization precision of as few as 2−3 bits. The research in [7] revealed that in multiple-input and multipleoutput (MIMO) systems with mixed-precision ADCs, equipping only a small proportion of high-resolution ADCs can closely approximate the achievable rate of conventional architecture with all full-resolution ADCs. These results inspired subsequent studies into signal recovery techniques for dealing with strong nonlinear distortion caused by coarse quantization.…”
Section: Introductionmentioning
confidence: 99%
“…The achievable rates and equalization with a mix of low and high-resolution ADC architecture with perfect Channel State Information (CSI) is discussed in [6]. The computational complexity of the proposed methods [5], [6] are in general high. In [7], low-complexity linear channel estimation and receive combiners for multiuser symbol detection were proposed and a lower bound on capacity was also derived using linear schemes.…”
Section: Introductionmentioning
confidence: 99%